1998
DOI: 10.1128/jvi.72.10.7772-7784.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immune Activation on the Dynamics of Human Immunodeficiency Virus Replication and on the Distribution of Viral Quasispecies

Abstract: Virus replication in a human immunodeficiency virus (HIV)-infected individual, as determined by the steady-state level of plasma viremia, reflects a complex balance of viral and host factors. We have previously demonstrated that immunization of HIV-infected individuals with the common recall antigen, tetanus toxoid, disrupts this steady state, resulting in transient bursts of plasma viremia after immunization. The present study defines the viral genetic basis for the transient bursts in viremia after immune ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 52 publications
(74 reference statements)
1
23
0
Order By: Relevance
“…Our laboratory has conducted a number of studies investigating the effects of cellular activation on HIV replication in vivo and found strong transient increases in viremia associated with tetanus toxoid immunization (73). In a later study, phylogenetic and phenotypic analyses of HIV quasispecies replicating during the peak of immunization-induced viremia revealed preferential expansion/replication of R5 viruses (13-fold increase) as compared to X4 viruses (no change) in an individual initially harboring both strains at equal frequencies (74). Furthermore, analyses of coreceptor expression in non-immunized HIV + and HIVsubjects (75) revealed that while the frequency of CD4 + CXCR4 + and CD4 + CCR5 + cells in HIV-infected subjects was comparable, the majority of activated (HLA-DR + ) CD4 + cells expressed CCR5 and not CXCR4.…”
Section: The Role Of Endogenous CC Chemokines In the Regulation Of Himentioning
confidence: 99%
“…Our laboratory has conducted a number of studies investigating the effects of cellular activation on HIV replication in vivo and found strong transient increases in viremia associated with tetanus toxoid immunization (73). In a later study, phylogenetic and phenotypic analyses of HIV quasispecies replicating during the peak of immunization-induced viremia revealed preferential expansion/replication of R5 viruses (13-fold increase) as compared to X4 viruses (no change) in an individual initially harboring both strains at equal frequencies (74). Furthermore, analyses of coreceptor expression in non-immunized HIV + and HIVsubjects (75) revealed that while the frequency of CD4 + CXCR4 + and CD4 + CCR5 + cells in HIV-infected subjects was comparable, the majority of activated (HLA-DR + ) CD4 + cells expressed CCR5 and not CXCR4.…”
Section: The Role Of Endogenous CC Chemokines In the Regulation Of Himentioning
confidence: 99%
“…The mechanism underlying this increase in viral replication is uncertain, and whether such observations are relevant in vivo is unknown. It is presumed that the immunisation related increase in plasma viraemia is a consequence of two factors: first, a transient increase in the susceptible pool of activated CD4 T-cell targets, and second an increase in pro-inflammatory cytokines secreted by these activated T cells, capable of inducing HIV expression from already infected but transcriptionally silent cells [24].…”
mentioning
confidence: 99%
“…The finding that there is no viral transmission between sero-different couples when the HIV-positive partner has HIV RNA levels below the threshold of 200 copies/mL [5] has led to the undetectable = untransmittable (U=U) campaign [6], which has reduced the stigma associated with HIV infection and promoted the retention in care of PLWHAs [7]. It is also well known that factors such as bacterial infections, influenza vaccinations and poor adherence to ART can cause a transient viral rebound that may not require a change in antiretroviral regimen: interestingly, Kolber et al found that seven of their 34 patients experienced a viral rebound after an influenza vaccination, two of whom showed RT and PR mutations [8][9][10][11], although it is not clear whether these were primary mutations or a spillover of previous archived mutations [10].…”
Section: Discussionmentioning
confidence: 99%